Urban Planning and Architectural Design Strategy for Disaster Response - Dr. Shagin Musa (International Journal of Advanced Science and Technology, 2020)
Since its inception, the globe has gone through a lot of disasters, including natural ones such as earthquakes, volcanoes, hurricanes, floods and desertification, including man-made since the industrial revolution and its impact on the environment, wars, conflicts and environmental and nuclear pollution through scientific and technological development, accompanied by an increase in the loss of lives, and social and economic consequences to be reckoned with. In it(1).With his accumulated experiences, man has been able to create the environment in which a person lives and practices his various activities and social and cultural activities to suit all his requirements, and legislation and standards came to regulate the processes of preservation and planning of this urban environment.This study examines the role of architectural planning in facing disasters and limiting the spread of the epidemic in the urban environment, and the role of government institutions in issuing defense laws, plans and forming committees to confront the epidemic, by highlighting the most important challenges, inventory and isolation of sites from which the epidemic is issued, as well as facing obstacles Faced by disaster planners, with the aim of developing proposals for a response plan for formal institutions and methods for testing them.